The Impact of Six Thinking Hats Strategy on Improving Creative Thinking Skills" Field research in the Medical City " - النعيمي, صلاح عبد القادر; محمد, غيداء حميد (Journal of Economics and Administrative Sciences, 2019)
Abstract     The research problem focuses on studying the interest of the Medical City Department of the Ministry of Health in improving the creative thinking skills of the administrative leadership through parallel & comprehensive thinking according to the of six thinking hats strategy. The research sample consisted of (170) administrative leaders in the upper & middle organizational levels, The questionnaire was used as a main tool for data collection, In addition to the observation & Interview, The research sought to answer the following questions: What is the extent to which the administrative leadership (Tpp & middle) in the organization investigated the concept of the six thinking hats strategy & creative thinking skills? How important is each of them? What is the relationship between the six thinking hats strategy & creative thinking skills? Are they associated with a fundamental relationship? In other words, the Six Thinking Hats strategy is in favor of improving the creative thinking skills of the sample.   The most significant results were : a significant difference in the perception of the top & middle administrative leadership of the six thinking hats strategy & the creative thinking skills resulting from the different organizational level & the middle administrative leadership & the existence of a positive medium relationship & significant significance between six thinking hats strategy & creative thinking skills & the highest correlation to these hats with creative thinking skills achieved by the green hat & white hat. The research came out with a number of recommendations , The most important of which were: to give formal attention to the six thinking hats strategy by the organization at the level of administrative leadership & its employees, to generalize & employ this strategy in the leadership activities, to embrace new & innovative ideas & to provide them with centers, Activate the role of the Organization's Training & Resource Development Division or the Training & Development Center for the Ministry of Health to contribute to the preparation of administrative leaders through the development of plans & the organization of intensive programs to develop their thinking, focusing on concepts Six thinking hats strategy, creative thinking skills & granting graduates certificates that qualify them to achieve leadership positions.